Teacher Creativity and Student Learning Interest as Determinants of Student Learning Outcomes in Elementary Schools - Aida Balqis; Didit Darmawan; Rizky Fitra Auliya (Sekolah Tinggi Agama Islam Al-Jami Banjarmasin, 2026)
This study aims to examine the relationship between teachers’ instructional creativity and students’ interest in learning as the main factors driving learning outcomes. Using a literature review design, this research conducts an in-depth analysis of various previous scientific discourses in order to formulate comprehensive and relevant conclusions. Data analysis was carried out qualitatively using secondary sources, with a focus on interpreting existing empirical findings. The results of the study indicate that teachers’ creativity in teaching and students’ high level of attention in learning are closely related to the achievement of academic competency standards. These findings confirm that the quality of primary education is strongly influenced by the balance between engaging instructional stimulation and consistent learning motivation.